Electronic structure evolution of Pd@Co nanocatalysts under oxidation and reduction conditions and preferential CO oxidation - Jain, Ruchi; Gopinath, Chinnakonda S. (ChemCatChem, 2020)
Herein, we present the surface electronic structure and morphological evolution under reduction and oxidation conditions for Pd@Co (PC) core-shell nanoparticles with different Pd : Co ratio (PC=2 : 1, 1 : 1 and 1 : 2). Extensive measurements have been made with NAPXPS (near ambient pressure x-ray photoelectron spectroscopy) under oxidising and reducing conditions, and ex-situ HRTEM. It has been demonstrated that PC catalysts are thermally stable towards morphological changes, at least up to 575 K. Nonetheless, it shows a significant surface electronic structure changes under reaction environments, which are highly relevant to heterogeneous catalysis. As expected, high (low) population of metallic (oxidised) Co was observed, while retaining core shell structure under reduction (H(2)and vacuum annealing) environment. Interestingly, the Pd-Co metallic interface helps to overcome the pyrophoric nature of cobalt and stabilised a significant amount of metallic Co at Pd-Co interface even in the presence of 0.1 mbar O(2)up to 575 K. The presence of Pd-Co and Pd-Co@Co(3)O(4)interfaces in reaction environment makes the catalyst dual functional. The proof of concept has been explored in terms of oxidation of CO in the presence of H(2)or O-2.
Keywords: Core-Shell morphology; Electronic Structure; heterogeneous catalysis; interface; XPS